Attributional style among youth at clinical risk for psychosis. Issue 1 (5th March 2012) - DeVylder, Jordan E.; Ben‐David, Shelly; Kimhy, David; Corcoran, Cheryl M.
Abstract Aim: A biased attributional style, in which negative events are attributed to external and personal causes, is associated with paranoid delusions in schizophrenia. It is not known whether this biased attributional style also characterizes individuals at clinical risk for psychosis or if it is associated with their emergent paranoia. Methods: Thirty‐three clinical high‐risk patients and 15 age‐ and gender‐similar controls were assessed with the Internal, Personal, and Situational Attributions Questionnaire for externalizing and personalizing attributional biases and for potential correlates with suspiciousness and other symptoms. Results: Both patients and controls had a similar external‐personalizing attributional style that was unrelated to symptoms, including suspiciousness. Conclusions: Consistent with other studies, a biased attributional style was not associated with subthreshold paranoia. Therefore, a biased attributional style is likely not a trait that contributes to emergent paranoid delusions but is instead a state‐dependent correlate of paranoid delusions.